Variabilidade espacial de agregados e carbono orgânico sob três diferentes usos de terra preta de índio no sul do Amazonas - Gomes, Romário Pimenta [UNESP]; Campos, Milton César Costa; Soares, Marcelo Dayron Rodrigues; Silva, Douglas Marcelo Pinheiro; Cunha, José Maurício; Franciscon, Uilson; Silva, Laércio Santos [UNESP]; Oliveira, Ivanildo Amorim; Brito, Wildson Benedito Mendes (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2017)
Indian Black Earths (IBEs) are distributed throughout the Amazon. They are characterized by their high chemical fertility and agricultural potential. IBEs have high organic carbon, favouring the improvement of soil structure. This work aimed to evaluate the aggregates and organic carbon (OC) spatial variability in different IBEs in southern Amazonas. We evaluated the organic carbon spatial variability, mean weight diameter (MWD), soil bulk density (ρb) and aggregate classes under three uses of soil: pasture, cocoa, and coffee. We collected 528 soil samples in a point grid according to its use at two depths: 0.0-0.05 m and 0.10-0.20 m. Results were subjected to variance, descriptive, and geostatistical analyses. We concluded that the soil use influenced the IBEs physical attributes soil behavior, concentrating the higher values of CO, aggregates > 2.00 mm, and MWD at 0.0-0.05 m in relation to ρb and aggregates < 2.00 mm where the higher values were the ones at 0.10-0.20 m. Aggregates < 2.00 mm (0.10-0.20 m) and OC (0.0-0.05 m) did not show spatial dependence, while the class of aggregates > 2.00 mm was the only attribute which represented to be a natural characteristic of the soil, with a strong spatial dependence, independently the land use and depth. There was no spatial relationship between the attributes studied and the geomorphic diversity.
Spatial variability of aggregates and organic carbon under three different uses of indian black earth in Southern Amazonas
Keywords: Aggregate classes; Land use; Soil aggregation; Spatial dependence